Innovation in the Utilization of Technology in Islamic Religious Education in Indonesian Schools - Achmad Musthofa; Riza Ashfari; Beni Zakaria; Malik Ashari; Khoiriyah (Education Reserach Center, 2026)
This research aims to comprehensively analyze innovation The Use of Technology in Islamic Religious Education (PAI) Learning in Indonesian Schools. Islamic Religious Education (PAI) in Indonesian schools still faces various fundamental problems. The implementation of technology is often limited to the use of instrumental digital learning media, without being accompanied by substantial pedagogic transformation. This study uses a descriptive qualitative approach with the method used in this study is library research (literature study). Data collection techniques are carried out through searching, collecting, and organizing scientific documents relevant to the focus of research. The data analysis in this study uses a content analysis model. The results of the study show that. 1. Learning videos are used in various formats, ranging from interactive lecture recordings, animations of Islamic materials. 2. VR technology is mainly used as an experiential-based learning medium to simulate religious practices and historical events in Islam. 3. The hybrid classroom model is implemented through a combination of face to face learning and online learning by utilizing various digital platforms. Research findings regarding the use of video-based learning technology, virtual reality, and hybrid classes in Islamic Religious Education (PAI) show that technological innovation not only has implications for the technical aspects of learning, but also reflects changes in pedagogic paradigms in religious education in Indonesian schools.